Investigation of Teachers' Sustainable Earthquake Awareness and Earthquake Knowledge Levels - Duygu Gür Erdoğan; Şeyda Şimşek (Sakarya University Journal of Education)
This research aims to examine the relationships between teachers' earthquake knowledge levels and sustainable earthquake awareness levels. A relational survey model with a quantitative research method was chosen for the research. The research group consists of 255 teachers, 166 women, and 89 men, working in private and public institutions in Kocaeli province in the 2022-2023 academic year. The research group was determined by convenient sampling, one of the purposeful sampling methods, and the "Sustainable Earthquake Awareness Scale" and "Earthquake Knowledge Level Scale" were used as data collection tools. The data of the research were analyzed in a particular statistical program using quantitative methods. As a result of the analysis, it was determined that teachers' sustainable earthquake awareness levels did not differ according to their gender and age, and while their earthquake knowledge levels did not differ according to their gender, they did vary according to their age. Additionally, it was observed that there was a positive relationship between teachers' earthquake knowledge levels and sustainable earthquake awareness levels.